A participação do estresse oxidativo e da inflamação na tolerância induzida pelo nitroprussiato de sódio - Mariana Cirillo Diniz (2012)
Organic nitrates are used in cardiovascular disorders therapeutics.However, chronic use of organic nitrates leads to tolerance, a phenomenon characterized by reduction of its hemodynamic and anti-ischemic effects. Tolerance to nitroglycerin has been widely investigated, however, little is known about tolerance to other nitrovasodilators, such as sodium nitroprusside. Thus, the aim of this study was to investigate the possible in vitro SNP-tolerance, characterizing its mechanisms and the role of oxidative stress and inflammation in this phenomenon. Results demonstrated that SNP-tolerance is time-dependent and endothelium-independent. Tolerant aortas showed increased O2- anions production due to NADPH oxidase activation and NO synthase uncoupling, by depletion of the substrate, L-arginine. Higher O2- anions concentration leads to activation of COX-2, inducing enhancement in vasoconstrictor production, such as PGF2 and TXA2, which negatively modulate the relaxation induced by SNP in tolerant aorta. In addition, it was observed a positive relationship between tolerance phenomenon and inflammatory process, characterized by increased p65/NF-KB subunit expression levels, as well as, inflammatory cytokines (TNF-ct and IL-6), contributing to vascular dysfunction, characteristic of tolerance phenomenon.